Correlation Analysis of Interleukin-6 on Blood Glucose in Prediabetes and Normal Glycemic Status - Ratih Feraritra Danu Atmaja; Theosobia Grace Orno; Tuty Yuniarty; Handayani Malik (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2023)
Diabetes mellitus is a global health problem whose incidence rate continues to increase yearly. Most people with diabetes mellitus go through the prediabetes phase. Prediabetes is a condition where blood glucose levels are elevated but have not yet reached the criteria for diabetes mellitus. Low-grade chronic inflammation is one of the pathways known to interfere with insulin signalling that ultimately affects blood glucose levels. One of the most studied inflammatory pathways in the pathogenesis of diabetes mellitus is interleukin-6 (IL-6). This study aims to determine whether there were differences in IL-6 levels between groups of prediabetes subjects and normal subjects and to observe the correlation between IL-6 levels and blood glucose. This study is useful in providing additional scientific evidence on the development of diabetes mellitus, especially in blood glucose regulation through inflammatory pathways. The design of this study was analytic observational in 71 subjects with prediabetes or normal glycemic status. Prediabetes status was established based on fasting blood glucose levels and glucose levels 2 hours post oral glucose tolerance test. Subjects with fasting blood glucose levels> 125mg/ dl and who had a fever in the last week were excluded from the study. Interleukin 6 levels were measured based on the principle of enzyme-linked immunoassay. The correlation of interleukin 6 with glucose levels and other variables was analyzed using the spearmen test. The results showed that interleukin 6 levels did not differ between the prediabetes group and the normal group ((5.27 ± 2.55 pg/ml) vs (4.44 ± 2.46) respectively; (p=0.105)). There was no correlation between interleukin 6 level and fasting blood glucose level (r=0.014, p=0.908) and glucose level after the oral glucose tolerance test (r=-0.085, p=0.480). In this study, there was a significant correlation between body mass index with waist circumference (r=0.772, p=0.000) and glucose levels after the oral glucose tolerance test (r=0.240; p<0.001). Recommends the addition of anti-inflammatory cytokines and variable insulin to assess further the effect of the inflammatory process on the glucose metabolism of subjects in future studies.